PENDEKATAN KONTEKSTUAL DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MAHASISWA PGMI (Studi Eksperimen Pada Mahasiswa PGMI Semester IV STAIN Jurai Siwo Metro TA. 2009/2010) - Annisah, Siti (P3M STAIN Jurai Siwo Metro, 2012)
AbstractÂ The purpose of this research is to know the difference between problem solving skill of students by using the contextual teaching learning and conventional learning.Â Â Â Â Â Â Â Â Â Â Â It is an experiment research. There are groups of the samples in this research, they are experiment and control groups. The experiment group learns the mathematics by using contextual teaching learning, while the control group learns the mathematics by using conventional learning. To get the data of this research, the researcher uses two kinds of instruments; test and observation. The subjects of this research are the students of PGMI STAIN Jurai Siwo in the fourth semester of the academic year 2009/2020.Â Â Â Â Â Â Â Â Â Â Â The result of this research is obtained after the treatments are given in experiment and control group. The result is there are significant difference between the students who learn mathematics by using contextual teaching learning and conventional learning.Based on the analysis of the data, it can be concluded that problem solving skill of students by using the contextual teaching learning is very different from conventional learning. In this research, it is known that the students who learn mathematics by using the contextual teaching learning are better than the students who learn by using conventional learning. They can build their knowledge actively, so they can find the concept or procedure of the mathematics (inquiry) by themselves. By this inquiry process, the studentsâ understanding about mathematics is more meaningful.Kata kunci: Contextual Teaching and Learning (CTL), and Problem Solving skill.